2007
DOI: 10.1007/s11695-007-9187-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Patterns in Hepatic Tissue and Visceral Adipose Tissue of Patients with Non-Alcoholic Fatty Liver Disease

Abstract: Our findings support the hypothesis that adipocyte secretion plays an important role in the development of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 28 publications
4
38
0
Order By: Relevance
“…Previous studies have examined gene expression changes in human NAFLD livers classified as steatotic (Greco et al, 2008) and in livers classified as NASH using various microarray platforms (Younossi et al, 2005a;Baranova et al, 2007;Rubio et al, 2007). These studies confirm that liver disease status alters gene expression changes.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have examined gene expression changes in human NAFLD livers classified as steatotic (Greco et al, 2008) and in livers classified as NASH using various microarray platforms (Younossi et al, 2005a;Baranova et al, 2007;Rubio et al, 2007). These studies confirm that liver disease status alters gene expression changes.…”
Section: Discussionsupporting
confidence: 55%
“…[10][11][12] In obese subjects, both pathways are stimulated by the soluble molecules produced by excessive white adipose tissue. Furthermore, many genes differentially expressed in the white adipose tissue of patients with NAFLD are linked to the processes of insulin resistance or inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many genes differentially expressed in the white adipose tissue of patients with NAFLD are linked to the processes of insulin resistance or inflammation. 11,12 It is possible that many of these targets are directly or indirectly regulated by miRNAs. Indeed, many molecules previously noted as differentially expressed in patients with NASH, such as V-rel reticuloendotheliosis viral oncogene homolog A (RELA) and STEAP family member 4 (STEAP4 ⁄ STAMP2), 13,14 have previously been identified in the miRanda database as potential targets of multiple miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In fact, in recent years, significant information in the understanding of NAFLD pathogenesis has been gained by examining the data accumulated by high-throughput technologies. 10,11 Often a single approach is not sufficient to give a comprehensive picture of hepatic dysfunctions occurring in NAFLD, and somewhat, a multiple-approach combination of different techniques is recommended. 12 Calvert et al 13 showed a good example of integration of system biology with reverse-phase protein microarray analysis to define genetic architecture of NAFLD.…”
mentioning
confidence: 99%